Interdisciplinary Approaches to Cultural Conservation: A Model for Sustainable Social Development - Sanmee, Wichian (Journal of Exploration in Interdisciplinary Methodologies (JEIM), 2025)
This paper explores interdisciplinary approaches to cultural conservation as a foundation for sustainable social development. In the face of globalization, urbanization, and environmental challenges, cultural heritage preservation requires the integration of diverse academic perspectives, including anthropology, environmental science, economics, and technology. By examining community-based conservation models, sustainable resource management, and digital documentation techniques, this study highlights the necessity of cross-disciplinary collaboration to enhance cultural resilience and identity. The research underscores the significance of stakeholder engagement, policy integration, and innovative technologies such as virtual reality and Geographic Information Systems (GIS) in preserving tangible and intangible heritage. Furthermore, the paper discusses how economic valuation and sustainable tourism practices can generate financial support for cultural conservation while maintaining ecological balance. By adopting a holistic framework that bridges scientific and local knowledge, this study advocates for inclusive and adaptive conservation strategies that align with sustainable development goals. The findings contribute to a broader understanding of how cultural heritage can be safeguarded while fostering social, economic, and environmental sustainability.